Adapted Weighted Aggregation in Federated Learning - Tang, Yitong (Proceedings of the AAAI Conference on Artificial Intelligence, 2024)
This study introduces FedAW, a novel federated learning algorithm that uses a weighted aggregation mechanism sensitive to the quality of client datasets, leading to better model performance and faster convergence on diverse datasets, validated using Colored MNIST.